1992
DOI: 10.1111/j.1399-302x.1992.tb00521.x
|View full text |Cite
|
Sign up to set email alerts
|

Glucosyltransferase phase variation in Streptococcus gordonii modifies adhesion to saliva‐coated hydroxyapatite surfaces in a sucrose‐independent manner

Abstract: Phase variation of Streptococcus gordonii between high (Spp+) and low (Spp-) levels of glucosyltransferase (GTF) activity resulted in the greater adhesion of Spp- strains to saliva-coated hydroxyapatite (S-HA) in a washed-cell adhesion test. Specific GTF mutants did not show this response. Although washed Spp+ cells produced 5-fold or more glucan from sucrose than Spp- cells did under the conditions of the adhesion test, sucrose elevated the adhesion of both phenotypes to hydroxyapatite (HA) equally, but had n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 15 publications
1
24
0
Order By: Relevance
“…Thus, Vickerman and Jones (42), using rabbit polyclonal antibody, identified PGP-LTA in strain C5, which had been received as S. oralis but which had also been shown to resemble S. gordonii phenotypically (41). Our data confirm the identity of strain C5 as a S. gordonii strain and also confirm that this organism produces PGP-LTA (Table 1).…”
Section: Resultssupporting
confidence: 77%
“…Thus, Vickerman and Jones (42), using rabbit polyclonal antibody, identified PGP-LTA in strain C5, which had been received as S. oralis but which had also been shown to resemble S. gordonii phenotypically (41). Our data confirm the identity of strain C5 as a S. gordonii strain and also confirm that this organism produces PGP-LTA (Table 1).…”
Section: Resultssupporting
confidence: 77%
“…We thus supplemented the salivary flow media with 1% sucrose, known to be sufficient in promoting Gtf activity-mediated biofilm formation (24, 25), and tested its effect on 24-h static biofilm growth in 96 well plates. Indeed, the crystal violet biofilm assay showed a greater biofilm biomass in single (p=0.005) and dual (p=0.0002) species biofilms formed by wild type S. gordonii CH1 in the presence of sucrose, compared to glucose (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Because the presence of GtfG protein enhances binding of S. gordonii to saliva-coated surfaces even in the absence of sucrose (25), we hypothesized that in the presence of saliva this enzyme may mediate initial binding to a preformed C. albicans biofilm. Therefore, we tested the ability of strains CH1, AMS12 and AMS12/pAMS40 to adhere to a preformed early C. albicans biofilm (4h) in saliva-supplemented media.…”
Section: Resultsmentioning
confidence: 99%
“…However, the bacterial pellicle may not fonn spontaneously and salivary masking may not occur until sufficient time has elapsed. Studies have also reported phase variation in cells grown in vitro versus cells grown in vivo (34). Thus It is possible that the indigenous bacteria will display different surface properties than the Haemophilus spp.…”
Section: I'orph Vroiuonas Gingivalis Atcc 33277 Atcc 25260mentioning
confidence: 99%